Karakteristik dan Studi Kasus Penerimaan Mi Sagu oleh Masyarakat di Sulawesi Selatan (Characteristics and Case Study of Sago Noodle's Acceptability by Consumer in South Sulawesi) - Endang Y. Purwani; Y. Setiawaty; H. Setianto; Widaningrum Widaningrum (agriTECH, 2006)
Noodle is the most popular product for the Indonesian people. It could be served conveniently without inferior image. Development of transparent noodle would promote consumption of saga Therefore, sago image as staple food would increase as superior as rice grain or wheat. The objectives of the research were to evaluate transparent noodle quality made from two types of sago starches and their acceptability by consumer (case: South Sulawesi). Noodle was prepared by mixing the thy sago starch with "binder" (completely gelatinized starch and additive) into dough. The dough was pressed manually through a container with holes in the base. Wet noodle was boiled in water and taken out of the water as soon as the strand floated, and were immediately transferred into cold water, and held before draining. Vegetable oil was added to avoid sticking. Sago (Metroxylon sago) starch were obtained from Pancasan Bogor and Palopo South Sulawesi, respectively. Noodle was then analyzed for quality and introduced to the consumers in South Sulawesi. They were represented by elementary school students (n=40), adults (n=40) and housewife (n=28). The result indicated that the physical characteristics of sago starch originated from Pancasan Bogor and Palopo were alike. However, they were different in term of starch pasting characteristics. Based on its raw material, Palopo starch showed the highest yield. Consumer's acceptability study indicated that transparent sago noodle was well accepted by more than 70% of consumers. The product contributed approximately of 7% of the daily calory intake (based on 2000 kkal RDI for Indonesian).